2023
DOI: 10.1002/ps.7426
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and antifungal evaluation of novel nopol derivatives as potent laccase inhibitors

Abstract: BACKGROUND To explore further potential natural product‐based antifungal agents, a series of novel nopol‐based carboxamide and hydrazide derivatives containing a natural pinene structure were designed, synthesized, and evaluated for their inhibitory activities against seven phytopathogenic fungi and oomycetes. RESULTS The bioassay results indicated that some compounds exhibited good inhibitory activities against Gibberella zeae, Sclerotinia sclerotiorum, and Phytophthora capsici. Among them, compound 3h displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Different concentrations compound 3 b (10.14 μmol/L, 5.07 μmol/L, 2.54 μmol/L, 1.23 μmol/L and 0.63 μmol/L), cysteine (82.54 μmol/L, 41.27 μmol/L, 20.63 μmol/L, 10.32 μmol/L and 5.16 μmol/L) and PMDD‐5Y (reported laccase inhibitor, 209.18 μmol/L, 104.59 μmol/L, 52.29 μmol/L, 26.15 μmol/L and 13.07 μmol/L) was tested for their laccase inhibitory activities. Specific test steps were consistent with our previous work [18] …”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…Different concentrations compound 3 b (10.14 μmol/L, 5.07 μmol/L, 2.54 μmol/L, 1.23 μmol/L and 0.63 μmol/L), cysteine (82.54 μmol/L, 41.27 μmol/L, 20.63 μmol/L, 10.32 μmol/L and 5.16 μmol/L) and PMDD‐5Y (reported laccase inhibitor, 209.18 μmol/L, 104.59 μmol/L, 52.29 μmol/L, 26.15 μmol/L and 13.07 μmol/L) was tested for their laccase inhibitory activities. Specific test steps were consistent with our previous work [18] …”
Section: Methodssupporting
confidence: 77%
“…The laccase inhibitory assay results and the docking study suggested that the target compounds could be potential laccase inhibitors [17] . Our group also designed and synthesized a novel series of nopol derivatives, and some derivatives exhibited potent antifungal and laccase inhibitory activities [18] . Although the research on laccase inhibitors is still in the preliminary stage, the discovery of this novel type of antifungal agents may offer a new approach for overcoming the emerging resistance of fungal pathogens to traditional antifungal agents [19]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some active compounds exhibited prominent antifungal and laccase inhibitory activities. 23 Natural products (NPs) have been considered as a huge treasury of lead compounds as well as inspirations for designing novel fungicides. 24 As an important renewable natural monoterpene, camphor can be isolated from Cinnamomum camphora, while the synthetic analogue can be produced from turpentine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, our group also reported novel nopol-based amide/hydrazide derivatives. Some active compounds exhibited prominent antifungal and laccase inhibitory activities …”
Section: Introductionmentioning
confidence: 99%